2011
DOI: 10.1007/s11094-011-0509-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antioxidant activity of new 1,2,4-triazole derivatives

Abstract: A series of new derivatives of 1,2,4-triazoles have been synthesized and their antioxidant properties have been studied. It was established that the obtained compounds exhibit a stabilizing effect on cell membranes and demonstrate antioxidant activity with respect to erythrocytes under oxidative stress conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…With the purpose to create new heterocyclic systems, to enlarge the range of heterocyclic compounds, as the research object we have chosen 5‐mercapto‐3,4‐disubstituted‐1,2,4‐triazoles ( 1 a‐h ), which are characterized by thion‐thiol tautomeric state. Hence, as the reactions of electrophilic substitution they result in both S‐substituted derivatives and Michael addition forming triazolyl‐substituted β‐alanines. And β‐alanine and its derivatives are known to be widely used as dietary supplementa (biologically active additives).…”
Section: Resultsmentioning
confidence: 99%
“…With the purpose to create new heterocyclic systems, to enlarge the range of heterocyclic compounds, as the research object we have chosen 5‐mercapto‐3,4‐disubstituted‐1,2,4‐triazoles ( 1 a‐h ), which are characterized by thion‐thiol tautomeric state. Hence, as the reactions of electrophilic substitution they result in both S‐substituted derivatives and Michael addition forming triazolyl‐substituted β‐alanines. And β‐alanine and its derivatives are known to be widely used as dietary supplementa (biologically active additives).…”
Section: Resultsmentioning
confidence: 99%
“…Benzimidazole derivatives have been a wide range of biological activities, such as analgesic 3 , antiinflammatory 4 , antiparasitic 5 , antitubercular 6 , antiviral 7 , anticonvulsant 8 and antimicrobial activities [9][10] . Literature survey indicated that the compounds consists of 1, 2, 4-triazole ring have been reported to possess different biological activities such as antimicrobial 11 , antifungal 12 , anti-inflammatory 13 , antioxidant [14][15] , antiviral 16 , anticancer 17 and anticonvulsant activity 18 depending on the substituent in the ring system. In view of such biological reports, the present work is aimed to design and develop the synthesis of some new potential substituted aryloxy triazolyl Benz [b] imidazole moiety and explores the evaluation of their in-vitro anthelmintic activity.…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 99%
“…For background to the biological activity of related compounds, see: Demirbas (2004); Demirbas et al (2009); Todoulou et al (1994); Kumar et al (2008); Kochikyan et al (2011); Singhal et al (2011); Popiołek et al (2013); Sraa (2012). For similar structures, see: Wu et al (2012); Pannu & Hundal (2011).…”
Section: Related Literaturementioning
confidence: 99%
“…Data collection: SMART (Bruker, 2000); cell refinement: SAINT (Bruker, 2000); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: SHELXTL/PC (Sheldrick, 2008); software used to prepare material for publication: SHELXTL/PC. (Demirbas et al, 2004 and2009;Kochikyan et al, 2011;Kumar et al, 2008;Singhal et al, 2011;Todoulou et al, 1994).…”
Section: Related Literaturementioning
confidence: 99%